The Impact of the Law: On Character Formation, Ethical Education, and the Communication of Values in Late Modern Pluralistic Societies - Witte, John; Welker, Michael (Evangelische Verlagsanstalt, 2021)
This volume addresses whether, how, and where laws (variously defined) teach values and shape moral character in late modern liberal societies. Each author recognizes the essential value of state law in fostering peace, security, health, education, charity, trade, democracy, constitutionalism, justice, and human rights, among many other moral goods. Each author also recognizes, however, the grave betrayals of law in supporting fascism, slavery, apartheid, genocide, persecution, violence, racism, and other forms of immorality and injustice. They thus call for state laws that set a basic civil morality of duty for society and for robust freedoms that protect private individuals and private groups to cultivate a higher morality of aspiration. With contributions by Rüdiger Bittner, Brian Bix, Frank Brennan, Allen Calhoun, Robert F. Cochran, Jr., Kenneth John Crispin, Jean Bethke Elshtain, E. Allan Farnsworth, James E. Fleming, M. Cathleen Kaveny, Ute Mager, Linda C. McClain, Reid Mortensen, Patrick Parkinson, Thomas Pfeiffer, Robert Vosloo, Michael Welker, and John Witte, Jr. [Der Einfluss des Rechts auf Charakterbildung, ethische Erziehung und Kommunikation von Werten in spätmodernen pluralistischen Gesellschaften] Dieser Band befasst sich mit der Frage, ob, wie und wo Gesetze – unterschiedlich formulierte – Werte lehren und den moralischen Charakter in spätmodernen liberalen Gesellschaften formen. Jeder Autor erkennt den wesentlichen Wert des staatlichen Rechts für die Förderung von Frieden, Sicherheit, Gesundheit, Bildung, Wohltätigkeit, Handel, Demokratie, Konstitutionalismus, Gerechtigkeit und Menschenrechten unter vielen anderen moralischen Gütern an. Jeder Autor erkennt jedoch auch den schwerwiegenden Verrat an Gesetzen an, der Faschismus, Sklaverei, Apartheid, Völkermord, Verfolgung, Gewalt, Rassismus und andere Formen von Unmoral und Ungerechtigkeit unterstützt. Sie fordern daher staatliche Gesetze, die eine grundlegende bürgerliche Pflichtmoral für die Gesellschaft festlegen, und robuste Freiheiten, die Privatpersonen und private Gruppen schützen, um eine höhere Moral des Strebens zu pflegen.